Surface Tracking on Polymeric Insulators Used in Electrical Transmission Lines - Ali Madi; Yadong He; Lilong Jiang; Baorui Yan (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Polymeric insulators need proper management and maintenance. Without proper management, the electric devices can be affected by factors such as leakages in the electricity system. In outdoor insulation, the environment subjects the material to a variety of stresses simultaneously that can lead to rapid degradation and loss of the insulation properties. Contamination of the surface of the insulating material, aging, electrical and mechanical stress are some of the forces that will result in the failure of the insulating material. To improve their reliability, research into the formulation of the material and the development of standards to eliminate creepage are being done. This work looks at the phenomenon of surface tracking. It investigates the actual process and looks at the possible types of surface tracking on polymeric insulators used under different environments. This also gives a short description of the emergence of polymeric insulators into the market.